A novel probabilistic image authentication methodbased on universal hash function for rgb images - Ozyurt, Fatih; Tuncer, Turker; Avci, Engin (Institute of Electrical and Electronics Engineers Inc., 2018)
In this paper, a novel hash based image authentication for RGB (Red, Green, Blue) images is proposed. Firstly, universal hash function is modified according to R, G and B layers and 3 different function is obtained to watermarking generation then, watermark generation is performed by using these equations. In this method, one layer is used for watermark embedding. Modulo based data hiding method is used for watermark embedding. To provide confidentiality of the proposed method, chaotic random number generator that is logistic map is used. The embedding layer and watermark generation function are selected by using logistic map. In watermark extraction, modulo operator is used. Watermark generation step is repeated for tamper detection. The extracted watermark and generated watermark are compared with each other. If these watermarks are equal, image is authenticated, otherwise tamper detection is detected. In the proposed method, DWT (Discrete Wavelet Transform) and SVD (Singular Value Decomposition) are used for generating perceptual hash of images and recovering images. Experimental result showed that the proposed method achieved high image authentication ability with minimum distortion. © 2018 IEEE.
2nd International Conference on Computing Sciences and Engineering, ICCSE 2018 -- 11 March 2018 through 13 March 2018 -- Kuwait City -- 137003
Keywords: Authentication; Discrete wavelet transforms; Hash functions; Number theory; Random number generation; Singular value decomposition; Wavelet decomposition; DWT (discrete wavelet Transform); Image authentication; Probabilistic images; Random number generators; SVD(singular value decomposition); Universal Hash Function; Watermark extraction; Watermark generations; Watermarking